2018
DOI: 10.3390/en11113105
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint Modeling of a Clinical Lab

Abstract: Modeling of a clinical lab carbon footprint is performed in this study from the aspects of electricity, water, gas consumption and waste production from lab instruments. These environmental impact indicators can be expressed in the form of the CO 2 equivalent. For each type of clinical test, the corresponding consumption of energy resources and the production of plastics and papers are taken into consideration. In addition, the basic lab infrastructures such as heating, ventilation, air-conditioning (HVAC) sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Reduced utilisation of equipment for tissue processing and use of laboratory stewardship can impact the carbon footprint and the waste generation in pathology laboratories 25. Use of multiple biopsy specimens (based on the clinical situation) in fewer cassettes might offer advantage after engaging in discussions with the pathologist 45. With increasing use of high-definition endoscopes, ability to inspect lesions with white-light and advanced imaging could potentially reduce the number of biopsy specimens especially in low yield conditions (small gastric fundic gland polyps, benign Brunner’s gland hyperplasia, hyperplastic lesions in the rectum, low-grade oesophagitis (Los Angeles oesophagitis grade A and B)) (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced utilisation of equipment for tissue processing and use of laboratory stewardship can impact the carbon footprint and the waste generation in pathology laboratories 25. Use of multiple biopsy specimens (based on the clinical situation) in fewer cassettes might offer advantage after engaging in discussions with the pathologist 45. With increasing use of high-definition endoscopes, ability to inspect lesions with white-light and advanced imaging could potentially reduce the number of biopsy specimens especially in low yield conditions (small gastric fundic gland polyps, benign Brunner’s gland hyperplasia, hyperplastic lesions in the rectum, low-grade oesophagitis (Los Angeles oesophagitis grade A and B)) (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical lab analyzed the energy needs of each device used for a specific method. 39 By adopting the usage time, the lab saved 30% of energy and carbon emissions without changing the method itself. The principles of green chemistry 42 and green analytical chemistry 43 can guide in the search for more sustainable methods.…”
Section: Sus Tainab Ilit Y In L Abor Atorie Smentioning
confidence: 99%
“…Switching off instruments can also have a significant impact. A clinical lab analyzed the energy needs of each device used for a specific method 39 . By adopting the usage time, the lab saved 30% of energy and carbon emissions without changing the method itself.…”
Section: Sustainability In Laboratoriesmentioning
confidence: 99%
“…Additionally, RDTs also decrease the carbon footprint by reducing the amount of energy needed for analysis and skipping the transportation of samples to the lab to complete the analysis. [15][16][17] The technology behind most commercially available rapid diagnostic tests mainly focuses on lateral flow assays (LFA) 18 and electrochemical methods. 19 LFAs have shown their potential in applications such as pregnancy tests and the detection of illegal drugs.…”
Section: Winnie E Svendsenmentioning
confidence: 99%
“…23 Furthermore, LFA tests are disposable with no need for additional chemicals, and using LFAs brings about a massive reduction of the carbon footprint by avoiding transportation of samples to the lab and the use of specialized equipment during analysis. 15 A recent study showed that the estimated CO 2 emissions of a single full-blood examination test done in a clinical lab were equivalent to driving a standard car for 770 m. 16,17 The success of electrochemical RDTs is centered around the amperometric glucose sensor's commercial success, an RDT used by millions of diabetic patients worldwide. 24 Electrochemistry has been suggested as a technique that could be used to develop RDTs to detect diseases in outbreaks.…”
Section: Winnie E Svendsenmentioning
confidence: 99%